Ergonomic Design of Hand Sanitizer Dispenser Stand With Foot Pedal Model - Sokhibi, Akh; Alifiana, Mia Ajeng; Asri, Vikha Indira (Spektrum Industri, 2022)
The COVID-19 pandemic that occurred in early 2020 until now is a new phenomenon in human life. Various sectors of life have been affected by the COVID-19 pandemic. To prevent the spread of the COVID-19 pandemic, the Government has made every effort, including appealing to avoid crowds, maintain distance, wear masks, limit mobility and diligently wash hands with water or hand sanitizer. Especially for the use of hand sanitizers placed in public places, tools are needed to place hand sanitizers that by the range of dimensions of the human body. So it is necessary to design a hand sanitizer stand by considering ergonomic aspects. Methods that have been used in this research was experimental with an ergonomic approach. The object of research is the design of a hand sanitizer dispenser stands with a foot pedal model by incorporating ergonomic aspects. The data collection procedure used is anthropometric data from the Javanese community. Then the anthropometric data were tested for normality, uniformity test, and data test. The design dimensions were obtained from percentile calculations based on anthropometric data. The results showed that the height of the bottle hand sanitizer stands was 91.73 cm; the hand sanitizer stand pedal width 13.67 cm; for the hand sanitizer stand, the pedal length is 24.32 cm.